357 Prostate-Specific Antigen (PSA) Screening Rates in the United States, 2009–2015: Implications for Practice Interventions. (11th January 2018) - Shahangian, Shahram; Fan, Lin; Taylor, Thomas
Abstract: Introduction: Prostate-specific antigen (PSA) is the most commonly used cancer screening test in men. Currently, there are two sets of recommendations for PSA screening: one championed by the US Preventive Services Task Force against screening of men of all ages, and the other by the American Cancer Society for offering screening only to 50- to 69-year-old men after informed/shared decision making. We evaluated PSA screening rates from 2009 through 2015. Methods: Claims for PSA screening of asymptomatic men, done by excluding PSA testing associated with 62 prostate or urinary conditions, were collected using Medicare (17.7–21.8 million men >64 years old) and MarketScan (9.9–16.5 million men 30–64 years old) databases. Trend tests were performed using a two-sided Poisson regression with Bonferroni correction. Results: Annual PSA screening rates were 2% in men aged 30–39, 13%-14% in men aged 40–49, 29%-31% in men aged 50–59, 33%-36% in men aged 60–64, 9%-13% in men aged 65–69, 11%-15% in men aged 70–74, and 9%-13% in men aged ≥75 years. Downward temporal trends were significant for ages 60–64 years ( P = .002) and 70–74 years ( P = .004). The 2009 to 2015 change in screening rate ranged from a decrease of 16% in men aged 70–74 years to an increase of 2% in men aged 30–39 years. Overall, PSA screening has decreased. Conclusions: Despite all recommendations against screening men aged <50 and >69, PSA screening is still performed in these age groups. In the >49 age group, PSA screening rate decreased presumably due to combined influence of all recommendations. There is a need to further understand why consensus recommendations for screening of men <50 and >69 are not fully followed. These results might also suggest continued opportunities for laboratory professionals to work with clinicians to implement only evidenced-based laboratory screening recommendations.